Career opportunities of local graduates in the plantation and commercial agriculture sector in Malaysia - Ahmad Anwar Mohamed Ismail; Marinah Muhammad; Aweng Eh Rak (2013)
The involvement of local graduates in the agriculture sector and in farming activities of the country is most crucial to boost the position of this sector as it is now ranked as the second largest contributor to the Gross Domestic Product (GDP), after gas and petroleum. A study was initiated to gauge the current status of carreer opportunities and job vacancies and job vacancies available in the plantation and commercial agricultural sector while at tha same time obtaining views from undergraduates of local universities of their expectation which can motivate them to venture into the agriculture sector upon graduation. This study was conducted on 20 leading plantations and commercial agricultural growers in Malaysia. The study involved conducting interviews with human resource managers through a survey questionnaire basically to identify issues and problems faced by the industry with regard job applicants from graduates of local institutions of higher learning and the vacancies made available by this particular sector on the job market. From the analyses made the study revealed that there exist a steady supply of vacancies but limited in number as positions in the managerial and professional field are far in between unlike the menial jobs commonly associated with the plantation industry. From the students perspective the acceptance level in the agricultural industry are not different from that in the manufacturing industries as graduates would prefer to seek jobs with the government or government linked companies. The findings from this study should be a basis for the policy makers especially MOHE to formulate a relevant recommendations in an effort to encourage more graduates to envolve in the agriculture sector. The results of the study should assist the private sector to relook at their policies and initiate new guidelines on attracting more graduates into their companies and thereby indirectly help the country to expand its agriculture base and move towards acheiving the target of making the agriculture sector the third engine of growth in the economy of the country.